The relationship between physical activity and sleep from mid adolescence to early adulthood. A systematic review of methodological approaches and meta-analysis. (August 2016) - Lang, Christin; Kalak, Nadeem; Brand, Serge; Holsboer-Trachsler, Edith; Pühse, Uwe; Gerber, Markus
Summary: Physical activity (PA) is considered an effective, non-pharmacological approach to improve sleep. However, the accurate measurement of PA and sleep among adolescents is fraught with challenges. Additionally, comparing the results of different studies is often difficult due to the diversity of assessment tools, analyses and data reporting procedures used. While previous reviews have considered variables that may confound this relationship, this systematic review examines the variations in measurement methods. Based on this overview, a meta-analysis was performed to assess possible influences of the various approaches on effect sizes. Twenty-one studies were included in the systematic review, of which 12 were appropriate for meta-analysis. For this, four subgroups were formed: subjective PA and subjective sleep, objective PA and subjective sleep, subjective PA and objective sleep, and objective PA and objective sleep. The majority of studies used subjective measures, often with unknown reliability or validity. Few studies employed objective tools to measure sleep. The results suggest that adolescents with higher subjective and objective PA are more likely to experience good sleep subjectively and objectively. More studies employing subjective and objective measures for both PA and sleep are needed. Researchers should take into account several assessment factors unique to the adolescent population.